Ovatodiolide: Recent Advances in Pharmacological Activities and Mechanisms - Zhou, Yingying; Zhang, Jianguo; Xia, Qingqing; Zhang, Lingmin; Zhang, Miaomiao; Lu, Lijun; Yang, Zaixing; Li, Jie (Planta Medica, 2025)
Ovatodiolide, a macrocyclic diterpenoid isolated from the traditional Chinese medicinal herb Anisomeles indica, exhibits diverse pharmacological activities in recent research. Its antitumor effects involve modulation of key signaling pathways (e.g., NF-κB/MMP-9, JAK2/STAT3, PI3K/AKT/mTOR, and Wnt/β-catenin) and effective targeting of cancer stem cells. For anti-fibrotic activity, it suppresses the TGF-β pathway and directly inhibits glucose-6-phosphate dehydrogenase. Additionally, it demonstrates antiviral, antibacterial, and anti-inflammatory activities. This review comprehensively summarizes current knowledge on ovatodiolide, including its discovery, synthesis, pharmacological actions, and underlying molecular mechanisms against target diseases. A deeper understanding of ovatodiolideʼs multifaceted pharmacological activities and mechanisms of action will accelerate its clinical translation as a therapeutic agent.
Keywords: ovatodiolide; Anisomeles indica; Labiatae; antimicrobial; antitumor; anti-inflammation; anti-fibrosis